Identification of the magnetic island structure in the HL-2A tokamak - 季小全 杨青巍 冯北滨 徐媛 孙腾飞 袁保山 (Chinese physics B, 2011)
The identification of the magnetic island structure in the HL-2A tokamak is presented. First, the perturbation current as a source for the perturbation flux can be determined by using Mirnov probe measurements. By superposing the perturbation flux and the equilibrium flux reconnected by equilibrium fitting, the structure and the width of the magnetic islands can be estimated. The method has been used in the HL-2A experiments.